Analysis of the relevance of antibiotic therapy and the experience of prescribers in the pediatric department at Bouaké University Hospital (Côte d'Ivoire) - Balayssac Eric Joseph; Djadji Ayoman Thierry Lenoir; Brou N'Guessan Aimé; Bertrand Sangbé; Assé Kouadio Vincent (Srpsko lekarsko drustvo, 2024)
Introduction: Infectious diseases, particularly among pediatric populations, represent a significant global health problems. Rational antibiotic use is paramount for achieving optimal patient outcomes, but prescribing antibiotics in pediatric settings is a multifaceted task influenced by various factors, including prescriber's knowledge and experience. Aim: This study, conducted at Pediatric Department at Bouaké University Hospital (Côte d'Ivoire) (CHU), aimed to investigate the relationship between prescriber's experience and the appropriateness of antibiotic prescriptions for pediatric patients. Material and Methods: The academic study lasted from June 1, 2019, to July 31, 2019, within the pediatric department of the Bouaké University Hospital. It included all children age 0 to 15 years, who were receiving antibiotic therapy for at least 48 hours. Evaluation of antibiotic therapy relied on criteria from authoritative references in infectious diseases. Antibiotic therapy was deemed appropriate if it was clinically justified for treating the specific infectious disease. Prescribers' experience-related variables, including years in medical practice, specialization level, and other pertinent factors, were integrated into the analysis to gain insights into their influence on the appropriateness and compliance of antibiotic prescriptions. Data analysis was executed using EPI INFO 2007 version 7.1.3.3 software, employing statistical tests such as Pearson's chi-square and Fisher's exact test. Results: The study unveiled that the incidence of antibiotic prescription among hospitalized children over the two-month period was 31.28%. Most prescribers had approximately 2 years of experience, with an average overall experience of 3.25 years. Male prescribers slightly outnumbered their female counterparts, and specialist physicians constituted the majority of prescribers (70.94%). Compliance was markedly higher among older children (46.76%) in comparison to infants (2.34%). Beta-lactam antibiotics were the most frequently prescribed class, accounting for 62.72% of antibiotic prescriptions. Non-compliance, particularly concerning dosage, was prevalent, contributing to 33.05% of cases, with betalactams being a prominent contributor. Conclusion: Although the influence of prescriber experience on antibiotic appropriateness remained inconclusive, the significance of rational antibiotic use remains pivotal. These findings underscore the necessity for continual efforts to optimize antibiotic therapy in pediatric care, endorsing evidence-based prescribing practices to safeguard the efficacy of antibiotics for future generations.